The impact of blood on liver metabolite profiling – a combined metabolomic and proteomic approach. (12th August 2013) - Ly‐Verdú, Saray; Schaefer, Alexander; Kahle, Melanie; Groeger, Thomas; Neschen, Susanne; Arteaga‐Salas, Jose M.; Ueffing, Marius; de, Martin Hrabe; Zimmermann, Ralf
ABSTRACT Metabolomics has entered the well‐established omic sciences as it is an indispensable information resource to achieve a global picture of biological systems. The aim of the present study was to estimate the influence of blood removal from mice liver as part of sample preparation for metabolomic and proteomic studies. For this purpose, perfused mice liver tissue (i.e. with blood removed) and unperfused mice liver tissue (i.e. containing blood) were compared by two‐dimensional gas chromatography time of flight mass spectrometry (GC × GC‐TOFMS) for the metabolomic part, and by liquid chromatography tandem mass spectrometry (LC‐MS/MS) for the proteomic part. Our data showed significant differences between the unperfused and perfused liver tissue samples. Furthermore, we also observed an overlap of blood and tissue metabolite profiles in our data, suggesting that the perfusion of liver tissue prior to analysis is beneficial for an accurate metabolic profile of this organ. Copyright © 2013 John Wiley & Sons, Ltd.